2017
DOI: 10.3389/fmicb.2017.00488
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Activity of a Self-Aggregating Peptide against Streptococcus mutans

Abstract: Streptococcus mutans is the primary agent of dental cavities, in large part due to its ability to adhere to teeth and create a molecular scaffold of glucan polysaccharides on the tooth surface. Disrupting the architecture of S. mutans biofilms could help undermine the establishment of biofilm communities that cause cavities and tooth decay. Here we present a synthetic peptide P1, derived from a tick antifreeze protein, which significantly reduces S. mutans biofilm formation. Incubating cells with this peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Other studies have shown that peptide P1 disrupts the architecture of Streptococcus mutans biofilm and can significantly decrease viable biofilm bacteria in an in vitro saliva-coated hydroxyapatite disc tooth model compared to a control peptide [15]. Although P1 can directly bind to bacterial cells, it shows no bactericidal activity.…”
Section: Mechanisms Of Anti-biofilm Peptides: Not Only Membrane Disrumentioning
confidence: 97%
See 4 more Smart Citations
“…Other studies have shown that peptide P1 disrupts the architecture of Streptococcus mutans biofilm and can significantly decrease viable biofilm bacteria in an in vitro saliva-coated hydroxyapatite disc tooth model compared to a control peptide [15]. Although P1 can directly bind to bacterial cells, it shows no bactericidal activity.…”
Section: Mechanisms Of Anti-biofilm Peptides: Not Only Membrane Disrumentioning
confidence: 97%
“…Biofilm-specific targets are slowly becoming increasingly recognized and investigated [15][16][17][18][19]. Original studies with LL-37 [14] indicated that this peptide acted by decreasing the attachment of bacterial cells, stimulating twitching motility, and influencing 2 major quorum sensing systems (Las and Rhl).…”
Section: Mechanisms Of Anti-biofilm Peptides: Not Only Membrane Disrumentioning
confidence: 99%
See 3 more Smart Citations